Address in the opening exercises of the academic year of [1866-1867]. - University of Santo Tomas, Manila; University of Santo Tomas, Manila. Discurso leido en la apertura anual de los estudios (Manila [publisher not identified])
Annual.
Available in microfilm at ISAIS Section see accession number (MCF-7850 ; MCF-7916)
Some address are published in Spanish.
Some issues have distinctive title.